Neglected patients with a neglected disease? A qualitative study of lymphatic filariasis. - Myrtle Perera; Margaret Whitehead; David Molyneux; Mirani Weerasooriya; Godfrey Gunatilleke (Public Library of Science (PLoS), 2007)
BACKGROUND: Lymphatic filariasis (LF) is a so-called neglected tropical disease, currently overshadowed by higher-profile efforts to address malaria, tuberculosis, and HIV/AIDS. Despite recent successes in arresting transmission, some 40 million people who already have the disease have been largely neglected. This study aims to increase understanding of how this vulnerable, neglected group can be helped. METHODS: We used purposive sampling to select 60 men and women with filarial lymphoedema (45 with filarial elephantiasis and 15 men with filarial hydrocoele) from the south of Sri Lanka in 2004-2005. Participants were selected to give a balance of men and women and poor and nonpoor, and a range of stages of the disease. Participants' experiences and the consequences of their disease for the household were explored with in-depth qualitative, semistructured interviews. FINDINGS: LF was extremely debilitating to participants over long periods of time. The stigma attached to the condition caused social isolation and emotional distress, and delayed diagnosis and treatment, resulting in undue advancement of the disease. Free treatment services at government clinics were avoided because the participants' condition would be identifiable in public. Loss of income due to the condition was reported by all households in the sample, not just the poorest. Households that were already on low incomes were pushed into near destitution, from which it was almost impossible to escape. Affected members of low-income households also had less opportunity to obtain appropriate treatment from distant clinics, and had living and working conditions that made hygiene and compliance difficult. SIGNIFICANCE: This highly vulnerable category of patients has low visibility, thus becoming marginalized and forgotten. With an estimated 300,000 total cases of elephantiasis and/or oedema in Sri Lanka, and around 300,000 men with filarial hydrocoele, the affected households will need help and support for many years to come. These individuals should be specially targeted for identification, outreach, and care. The global strategy for elimination is aimed at the cessation of transmission, but there will remain some 40 million individuals with clinical manifestations whose needs and problems are illustrated in this study.